Congenital Lung Abnormalities: Experience of a Tertiary Care NICU in Delhi, A Case Series. Issue 1 (March 2022) - Kukreja, Bhavya; Mittal, Deepak; Sidana, Poonam; Sikka, Gurleen; Wardhan, Harsh; Mehta, Ajay Prakash
Respiratory distress is the most common cause of neonatal admission. Cystic lung lesions are rarer cause of the same. These are heterogeneous lesions with varied antenatal and postnatal manifestations. The outcomes of antenatally diagnosed lung malformations have showed more improvement than previously thought of. With advancement in imaging techniques, more definitive diagnosis and timely intervention, even in-utero interventions, can be planned. Overall, survival rates have also improved over the past 2 decades. A majority of infants are asymptomatic and do not require surgery in neonatal period, and the expectant management is usually followed in most centers, but some may have mass effect and require either in-utero or early neonatal intervention. For asymptomatic lesions, the timing of surgery remains controversial as there are propagators of both early and late intervention. A multidisciplinary team approach is required for its optimal management. We present here a set of 3 babies who were diagnosed as having cystic lung lesions antenatally but later these turned out to be completely different entities.